c-MET and the immunological landscape of cancer: novel therapeutic strategies for enhanced anti-tumor immunity - Jabbarzadeh Kaboli, Parham; Roozitalab, Ghazaal; Farghadani, Reyhaneh; Eskandarian, Zoya; Zerrouqi, Abdessamad (Frontiers in Immunology, 2024)
Cellular mesenchymal-epithelial transition factor (c-MET), also known as hepatocyte growth factor receptor (HGFR), is a crucial receptor tyrosine kinase implicated in various solid tumors, including lung, breast, and liver cancers. The concomitant expression of c-MET and PD-L1 in tumors, such as hepatocellular carcinoma, highlights their prognostic significance and connection to therapeutic resistance. Cancer-associated fibroblasts and mesenchymal stromal cells produce hepatocyte growth factor (HGF), activating c-MET signaling in tumor cells and myeloid-derived suppressor cells (MDSC). This activation leads to metabolic reprogramming and increased activity of enzymes like glutaminase (GLS), indoleamine 2,3-dioxygenase (IDO), and arginase 1 (ARG1), depleting essential amino acids in the tumor microenvironment that are vital for effector immune cell function. This review highlights the interplay between tumor cells and myeloid-derived suppressor cells (MDSCs) that create an immunosuppressive environment while providing targets for c-MET-focused immunotherapy. It emphasizes the clinical implications of c-MET inhibition on the behavior of immune cells such as neutrophils, macrophages, T cells, and NK cells. It explores the potential of c-MET antagonism combined with immunotherapeutic strategies to enhance cancer treatment paradigms. This review also discusses the innovative cancer immunotherapies targeting c-MET, including chimeric antigen receptor (CAR) therapies, monoclonal antibodies, and antibody-drug conjugates, while encouraging the development of a comprehensive strategy that simultaneously tackles immune evasion and enhances anti-tumor efficacy further to improve the clinical prognoses for patients with c-MET-positive malignancies. Despite the challenges and variability in efficacy across different cancer subtypes, continued research into the molecular mechanisms and the development of innovative therapeutic strategies will be crucial.